Truman Defeats Dewey - Donaldson, Gary (Book collections on Project MUSE., 1999)
Fifty years ago Harry S. Truman pulled off the greatest upset in U.S. political history. With his party split on both the left and the right, and facing a formidable Republican opponent in New York governor Thomas E. Dewey, the Missourian was thought to have little chance of remaining in the White House. But politics in the postwar years were changing dramatically. Truman and his advisers successfully read those changes: their strategy focused on building a coalition of organized labor, African Americans in large northern cities, and traditional liberals--and ignoring protests from the conserv.